Smiley's people [videorecording (DVD)] - Langton, Simon; Paterson, Bill, 1945-; Atkins, Eileen; Stewart, Patrick, 1940-; Guinness, Alec, 1914-2000; Le Carré, John, 1931- (Acorn Media, 2011)
This brilliant sequel to 'Tinker, Tailor, Soldier, Spy' finds Smiley emerging from retirement to engage his lifelong nemesis, the Soviet spymaster Karla, in a final test of wits, nerves, and loyalties. Stellar ensemble casts bring John le Carre's thrilling tales of Cold War-era espionage to vivid life in these television classics.